2016
DOI: 10.2116/analsci.32.343
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Retention of Chelating Reagents in Octadecylsilyl Silica Phase by Interaction with Residual Silanol Groups in Solid Phase Extraction of Divalent Metal Ions

Abstract: Solid-phase extraction (SPE) of divalent metal ions with a lipophilic and potentially divalent hexadentate chelating reagent (H2L), with which octadecylsilyl silica (ODS) was impregnated, was studied to gain more insight into and develop the potential of this methodology. This is the first time to demonstrate that this reagent as well as other common nitrogencontaining reagents were retained both by adsorption due to hydrogen bonding between nitrogen atoms of the reagent and residual silanol groups in the ODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The silica gel SG showed negligibly small retention. Both the isotherms suggested substantially the same characteristics as those of nitrogen-containing compounds, 12 and were thus fitted by Eq. 3as the sum of a simple distribution term and a Langmuir adsorption term by hydrogen bonding between oxygen atom of R and silanol hydrogen:…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The silica gel SG showed negligibly small retention. Both the isotherms suggested substantially the same characteristics as those of nitrogen-containing compounds, 12 and were thus fitted by Eq. 3as the sum of a simple distribution term and a Langmuir adsorption term by hydrogen bonding between oxygen atom of R and silanol hydrogen:…”
Section: Resultsmentioning
confidence: 90%
“…11 In a previous work, we have studied the retention of a certain nitrogen-containing compound in an ODS silica subjected to sufficient endcapping treatment and an ODS silica with silanol intentionally left, under ambient pressure. 12 This study has revealed that residual silanol enhances the wettability of the ODS silica even in the absence of any water-miscible organic solvent, that the retention of the compound may be attributed to the sum of the…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…22,23 In a previous work, we demonstrated that a hexadentate chelating reagent dissolved in toluene was retained on ODS silica as the sum (defined afresh as retention including isotherms within this paper) of the simple distribution to the ODS phase and the Langmuir adsorption to residual silanol group mechanism. 24 A large amount of the reagent could be retained on the ODS silica containing a large amount of residual silanol by virtue of the Langmuir adsorption term. In the retention of acetylacetone and its metal complex from the aqueous phase on the ODS phase, it was reported that the residual silanol group improves the wettability of the ODS phase and is the donor of the ligand and the metal complex.…”
Section: Introductionmentioning
confidence: 99%